Barriers to the provision of optimal care to dying patients in hospital: An international cross-sectional comparison study of nurses' perceptions. Issue 1 (February 2022) - Shepherd, Jan; Waller, Amy; Chan, Sally; Kim, Miyoung; Kang, Sook Jung; Chan, Carmen; Chow, Meyrick; Clapham, Matthew; Sanson-Fisher, Rob
Abstract: Background: Nurses play an important role in caring for patients who are dying in hospital, so it is important to understand their perceptions of the factors that may influence the quality of that care. Much of the existing literature is focused on end-of-life care provision in western settings. Little is known about how nurses' perceptions of end-of-life care provision may differ across Asian and Western locations. Understanding the similarities and differences between the perceptions of nurses in Asian and Western locations about the barriers to the provision of high-quality end-of-life care may help guide education and policy initiatives to improve end-of-life care in each location. Aim: To compare the perceptions of nurses from Australia, South Korea, and Hong Kong regarding barriers to high-quality end-of-life care provision for people dying in hospitals. Methods: A cross-sectional study of hospital-based nurses from Australia (n = 153), South Korea (n = 241), and Hong Kong (n = 188) completed a survey between December 2016 and June 2018. Nurses indicated the extent to which they perceived 40 items across five domains to be a barrier to high-quality end-of-life care provision. Findings: Significant variation between the perceptions of nurses in each location was found in two-thirds of the survey items. The greatest difference was seen in the item doctors continue life-sustaining medical interventions for too long, which was considered a significant barrier by 60.1% of Australian nurses, 32.9% of South Korean nurses and 13.8% of Hong Kong nurses. The greatest cross-location agreement related to differences in religious beliefs and languages. These items were considered a significant barrier by fewer than one-quarter of nurses. Conclusion: Nurses in Hong Kong, South Korea and Australia perceived a range of challenges to the provision of optimal end-of-life care. The significant differences observed in two-thirds of response items support the hypothesis that strategies to improve the quality of end-of-life care in one location may not be effective in another. For interventions to be effective they must be tailored to the unique nature of care-provision in each location. Gaining an understanding of the potential reasons for these differences may highlight potential targets for interventions that address the unique factors associated with care provision in each location.